Corrigendum to "Amaranth and buckwheat grains: Nutritional profile, development of functional foods, their pre-clinical cum clinical aspects and enrichment in feed" [Current Research in Food Science, (9), 2024, 100836] - Kumar, Harsh; Guleria, Shivani; Kimta, Neetika; Dhalaria, Rajni; Nepovimova, Eugenie; Dhanjal, Daljeet Singh; Alomar, Suliman Y; Kuca, Kamil (Current research in food science, 2025)
[This corrects the article DOI: 10.1016/j.crfs.2024.100836.].